Results of neuroblastoma treatment in Lithuania: a single centre experience - Juškaitė, Austėja; Tamulienė, Indrė; Rascon, Jelena (Acta medica Lituanica, 2017)
Background. Neuroblastoma (NB) is the most common extracranial solid tumour in children. This is a very rare disease with heterogeneous biology varying from complete spontaneous regression to a highly aggressive tumour responsible for 15% of malignancy-related death in early childhood. Analyses of survival rates in Europe have shown a considerable difference between Northern/Western and Eastern European countries. Treatment results of NB in Lithuania have never been analyzed. Aim. To assess the survival rate of children with NB according to initial spread of the disease, age at diagnosis, the MYCN amplification, risk group, and treatment period. Patients and methods. A retrospective single-centre analysis of patients’ records was performed. Children diagnosed and treated for NB between 2000 and 2015 at the Centre of Paediatric Oncology and Haematology of the Children’s Hospital, Affiliate of Vilnius University Hospital Santaros Klinikos were included. The patients were divided into three groups according to the spread of the disease: group 1 – patients with local NB older than 12 years of age; group 2 – stage IV patients, also called the M stage; group 3 – infants with stages 4S and MS. The patients were stratified into three risk groups – low, intermediate and high risk. Estimates of five-year overall survival (OS5y) were calculated using the Kaplan-Meier method comparing survival probability according to spread of the disease, age at diagnosis, the MYCN amplification, risk group and treatment period (2000–2007 vs 2008–2015). Results. Overall 60 children (31 girls and 29 boys) with NB were included. The median age at diagnosis was 1.87 years (ranged from 4 days to 15 years). Seventy-eight percent of cases were found to be differentiated or undifferentiated NB, 22% – ganglioneuroblastoma. The local form of the disease was predominant: 57% (34/60) of patients were allocated to the group 1, 37% (22/60) with initial metastatic disease were assigned to group 2, and infants with 4S or MS stage comprising 7% (4/60) allocated to group 3, respectively. The probability of OS5y for the entire cohort was 71% with the median follow-up of 8.8 ± 4.8 years. The probability of OS5y for local disease (group 1) was significantly higher compared to metastatic disease (group 2) (94% vs. 34%, p = 0.001, respectively) as well as for infants compared to children older than 12 months at the time of diagnosis (90% vs 60%, p = 0.009, respectively). The MYCN gene amplification had a negative influence on OS5y, with 78% of MYCN-negative patients surviving in comparison to 40% of MYCN-positive patients who did not survive (p = 0.153). The high-risk patients had significantly worse OS5y than children with intermediated or low risk (35% vs. 82% vs. 100%, respectively, p = 0.001). Comparison of OS5y between two treatment periods in the entire patient population revealed a non-significant increase in survival from 66% in the 2000–2007 period to 82% in the 2008–2015 period (p = 0.291), mostly due to a dramatic improvement achieved for high-risk patients whose survival rate increased from 9% in the 2000–2007 period to 70% in the 2008–2015 period (p = 0.009). Conclusions. There was a slight predominance of low-risk patients, probably due to a higher number of infants. A better probability of OS5y was confirmed in infants with local disease and in MYCN-negative patients. The OS5y for children treated for NB at our institution over 16 years increased from 66% in the 2000–2007 period to 82% in the 2008–2015 period with the most significant improvement achieved for high risk patients. The current survival rate of children treated for NB at our institution is in line with the reported numbers in Northern and Western European countries.